Cultural understanding of ‘spiritual well-being’ and ‘psychological well-being’ among Sinhalese Buddhists in Sri Lanka - Udayanga, Samitha (Sri Lanka Journals Online (JOL), 2021)
The influence of culture in conceptualising ‘wellbeing’ has important implications for human health. Culture influences how individuals experience, conceptualise and reflect on the health behaviour. This study thus explores how Sinhalese Buddhists, who follow Sinhalese medicine in Sri Lanka, conceptualise spiritual and psychological well-being as experienced in their culture. In-depth interviews and focus group discussions with twenty-seven participants and empirical observations in four temples revealed that practices that lead to spiritual well-being are embedded in their everyday lives and are conceptualised as internal qualities that facilitate people to interact with the outside world with a proper mode of thought. Psychological well-being is perceived as an ability to achieve whatever that brings happiness to their life. This study thus indicates that although Sinhalese Buddhists in Sri Lanka are less likely to articulate the difference between psychological well-being and spiritual well-being, they are aware of the very existence of spiritual well-being and psychological well-being.
Keywords: Cultural understanding; Lay experiences; Psychological well-being; Sinhalese Buddhist community; Sinhalese medicine; Spiritual well-being